Survival of Rainbow Trout fry in the wild: a comparison of two whirling disease resistant strains - Avila, Brian Walter, author; Winkelman, Dana L., advisor; Angeloni, Lisa M., committee member; Fetherman, Eric R., committee member; Myrick, Christopher A., committee member (Colorado State University. Libraries, 2016)
Many animal populations have experienced population declines due to a broad range of factors such as habitat loss and degradation, invasive species, disease, and climate change. Introduced pathogens are known to have dramatic effects on populations. Following the establishment of the parasite that causes whirling disease (Myxobolus cerebralis) in Colorado, Colorado Parks and Wildlife (CPW) developed a whirling disease resistant Rainbow Trout (Oncorhynchus mykiss) for stocking known as the GRxCRR. The GRxCRR is a cross between the wild, susceptible Colorado River Rainbow (CRR) and the domesticated, resistant German Rainbow (GR) trout strains. It was thought that the GRxCRR would exhibit survival and reproduction similar to that of the CRR, overcome potential disadvantages associated with the history of domestication of the GR, and maintain the genetic resistance to whirling disease of the GR. One disadvantage to stocking GRxCRR is the potential for outcrossing and backcrossing that could decrease resistance to whirling disease. Stocking pure GR was not considered a viable option because it was thought that they would not survive well in a natural environment. However, in a laboratory study the GR and GRxCRR strains showed few physiological differences, indicating that the GR may be a candidate for stocking in whirling disease positive streams. I undertook a laboratory and field experiment to compare fry survival between the two strains. The field experiment was conducted in three drainages (Cache la Poudre River, Middle Fork of the South Platte River, and Colorado River), and three streams were selected in each drainage. One-mile reaches of each stream were stocked in August 2014 with 5,000 GRxCRR, identified with coded wire tags, and 5,000 untagged GR. In October 2014, April 2015 and August 2015, population estimates were conducted, providing an estimate of apparent survival for each strain. Two laboratory experiments were also conducted. In the first experiment, a 50:50 mix of GRxCRR and GR were stocked into large open mesocosms with one wild Brown Trout (Salmo trutta) predator. Survival was estimated over a 24-hour time period. The second experiment was similar, but I added treatments with or without cover. The field experiment revealed that apparent survival and growth rate was influenced by strain, stream, and primarily average temperature within the first year after stocking. After two months in the wild, the GRxCRR exhibited a higher growth rate than the GR, opposite of what is seen in the hatchery. However, after 12 months there was no significant difference in apparent survival or growth rate between the GR and GRxCRR. Laboratory experiments revealed that there were no differences in survival between the strains when confronted with Brown Trout predation. My results indicate that the GR may be a viable alternative for stocking in streams that contain M. cerebralis.